Tyrosine 263 in Cyanobacterial Phytochrome Cph1 Optimizes Photochemistry at the prelumi‐R→lumi‐R Step. (28th March 2014) - Sineshchekov, Vitaly; Mailliet, Joel; Psakis, Georgios; Feilke, Kathleen; Kopycki, Jakub; Zeidler, Mathias; Essen, Lars‐Oliver; Hughes, Jon
Abstract We report a low‐temperature fluorescence spectroscopy study of the PAS‐GAF‐PHY sensory module of Cph1 phytochrome, its Y263F mutant (both with known 3D structures) as well as Y263H and Y263S to connect their photochemical parameters with intramolecular interactions. None of the holoproteins showed photochemical activity at low temperature, and the activation barriers for the Pr→lumi‐R photoreaction (2.5–3.1 kJ mol−1) and fluorescence quantum yields (0.29–0.42) were similar. The effect of the mutations on Pr→Pfr photoconversion efficiency (ΦPr→Pfr) was observed primarily at the prelumi‐R S0 bifurcation point corresponding to the conical intersection of the energy surfaces at which the molecule relaxes to form lumi‐R or Pr, lowering ΦPr→Pfr from 0.13 in the wild type to 0.05–0.07 in the mutants. We suggest that the Ea activation barrier in the Pr* S1 excited state might correspond to the D‐ring (C19) carbonyl – H290 hydrogen bond or possibly to the hindrance caused by the C131/C171 methyl groups of the C and D rings. The critical role of the tyrosine hydroxyl group can be at the prelumi‐R bifurcation point to optimize the yield of the photoprocess and energy storage in the form of lumi‐R for subsequent rearrangement processes culminating in Pfr formation.